2013
DOI: 10.3109/00016357.2012.757358
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic effect of benzocaine mucoadhesive patches on orthodontic pain caused by elastomeric separators, a preliminary study

Abstract: The recorded mean VAS values were relatively low; however, the benzocaine 20% patches significantly reduced the post-separation orthodontic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 44 publications
2
28
2
Order By: Relevance
“…Furthermore, there were some other limitations in our present study. We used the NRS scale to rate the feeling of pain, and thus the patients' assessments were subjective [38,39]. Therefore, further research should be carried out to search for more objective pain assessment methods during orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there were some other limitations in our present study. We used the NRS scale to rate the feeling of pain, and thus the patients' assessments were subjective [38,39]. Therefore, further research should be carried out to search for more objective pain assessment methods during orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary study analyzed the effect of benzocaine mucoadhesive patches on orthodontic pain caused by elastomeric separators. It was revealed that the use of 20% benzocaine patches during the first 3 days after the separator placement significantly decreased the degree of pain [29]. This finding triggered the interest to investigate the effect of the lidocaine/prilocaine topical anesthetic, Oraqix®, on pain reduction from the initial placement of orthodontic separators.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies revealed the superior efficacy and fast onset of action of benzocaine as anaesthetic agent to mucous membranes when compared to e.g. lidocaine or to placebo (4)(5)(6)(7)(8)(9)(10)(11)(12). Some other studies describe no significant differences in efficacy between benzocaine and the comparator topical anaesthetic administered on mucous membranes, even though pain reduction has been observed (13)(14)(15).…”
Section: Introductionmentioning
confidence: 91%